A railway-like network electrode design for room temperature Na–S battery. Issue 1 (4th December 2018) - Yang, Tingting; Gao, Wei; Guo, Bingshu; Zhan, Renming; Xu, Qiuju; He, Hong; Bao, Shu-Juan; Li, Xiaoyan; Chen, Yuming; Xu, Maowen
Abstract : A 3D railway-like electrode design to tackle the poor conductivity and severe volume expansion in a room temperature Na–S battery. Abstract : Poor conductivity and severe volume expansion of sulfur (S) electrode are the key issues for the practical application of room temperature Na–S battery. In this paper, we propose a 3D railway-like electrode design to tackle these problems for room temperature Na–S battery. Nitrogen-doped porous carbon polyhedrons (NPCs) as "station" for loading S are tightly concatenated by 1D carbon nanotubes (CNTs) as "railway" for transporting electrons to form a 3D railway-like network (CNT/NPC) as S host. The 3D cross-linked railway-like network not only facilitates the rapid transfer of electrons for high capacity but also connects the polyhedrons during the cycling maintaining the integrity of the electrode. With this rational design, 3D railway-like S@CNT/NPC electrode shows a high discharge capacity of ∼601 mA h g −1 at 0.5C and outstanding rate capability. In addition, a high capacity of 410 mA h g −1 can still be achieved after 500 cycles with a very low capacity decay rate of 0.064% per cycle.